Implementing Group Investigation to Learn Reading for Senior High School Students - Maleng, Ana Valentine; Hartati, Elysa (Language Circle: Journal of Language and Literature, 2021)
Students’ boredom when it comes to reading long texts gives an impact on their comprehension of the text’s main idea due to the use of traditional teaching and learning techniques. Therefore, this study aims to describe how Group Investigation (GI) is implemented in teaching reading, as well as to find out the students’ responses toward GI in learning reading. This research focuses on finding out the evidence of how far the method affects students reading ability. The mixed-method between qualitative and quantitative approaches were used to conduct this research. The data obtained were from observation, questionnaire, interview, and documentation. The GI was conducted with group discussion and peer review. The result showed that 84.21% of students gave positive respond toward GI implementation. Based on the interview, students felt they were more motivated, engaged, and enjoyed during the reading skill lesson. Thus, GI is a good alternative to learn reading and help students’ reading comprehension as well as the class environment to be more active and joyful.